2014
DOI: 10.1371/journal.pone.0099043
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects of Long-Term Air Pollution Exposure and Variants in the GSTP1, GSTT1 and GSTCD Genes on Risk of Acute Myocardial Infarction and Hypertension: A Case-Control Study

Abstract: IntroductionExperimental and epidemiological studies have reported associations between air pollution exposure, in particular related to vehicle exhaust, and cardiovascular disease. A potential pathophysiological pathway is pollution-induced pulmonary oxidative stress, with secondary systemic inflammation. Genetic polymorphisms in genes implicated in oxidative stress, such as GSTP1, GSTT1 and GSTCD, may contribute to determining individual susceptibility to air pollution as a promoter of coronary vulnerability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…4,5,10,12,[23][24][25][26][27][28][29] We used a standardized table to extract the following information from all of the included articles: authors, publication year, study setting, study population, study duration, study design, short-term or long-term effect, exposure measurement method, data source, number of controls and cases, type of air pollution, exposure mean and range, adjusted odds ratio (OR) and their 95% confidence intervals (CIs), adjusted covariates, and the number of lag days for short-effect if applicable. Eligibility assessments and all of the data extraction were checked and verified by consensus of the 2 investigators.…”
Section: Data Extractionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,5,10,12,[23][24][25][26][27][28][29] We used a standardized table to extract the following information from all of the included articles: authors, publication year, study setting, study population, study duration, study design, short-term or long-term effect, exposure measurement method, data source, number of controls and cases, type of air pollution, exposure mean and range, adjusted odds ratio (OR) and their 95% confidence intervals (CIs), adjusted covariates, and the number of lag days for short-effect if applicable. Eligibility assessments and all of the data extraction were checked and verified by consensus of the 2 investigators.…”
Section: Data Extractionmentioning
confidence: 99%
“…Of the 17 included studies, 3 studies defined hypertension as systolic blood pressure ≥140 mm Hg and diastolic blood pressure ≥90 mm Hg 4,24,25 ; 5 studies defined hypertension according to the ICD9 or ICD10 code [6][7][8][9]21 ; 2 studies used self-reported doctor-diagnosed hypertension 5,27 ; and 7 studies used >1 methods to define the hypertension cases 10,12,21,23,26,28,29 ( Tables 1 and 2). …”
Section: Definition Of Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, genes belonging to the glutathione S-transferase (GST) family are of particular interest because of their role in cellular protection against oxidative stress, which is a potential pathway for toxic air pollution effects. 12 Recently, evidence has found that children with GST pi 1 (GSTP1) and GST Mu 1 (GSTM1) genotypes may constitute a susceptible population at increased risk of asthma associated with TRAP 13,14 and of childhood AD associated with prenatal smoke exposure. 15 In addition, there is growing evidence that air pollutants activate Toll-like receptor (TLR) signaling, resulting in a pro-inflammatory response in the lung, 16 and a previous study in the PIAMA cohort identified a gene by TRAP interaction for TLR2 and TLR4 variants with respect to asthma.…”
Section: Introductionmentioning
confidence: 99%